Current Nordic research on the Malay world: A bibliographical sketch - Ooi, Kee Beng (Universiti Kebangsaan Malaysia, 2003)
As interest in Southeast Asia increases in tandem with the region’s economic development, and lately as a result of global tensions, Islam as cultural and political factor is now of such importance that the academic division of Southeast Asia into a northern and a southern part appears unavoidable. The latter is characterized by links to the Muslim world and beyond, while the former is not. Nordic research on the Malay World investigates a wide range of subjects, and the heterogeneity of the region has inspired theoretical models in many academic disciplines. Malay World studies are thus more than the mere construction of knowledge about Malay society